ANALISIS ISI OBJEKTIVITAS PEMBERITAAN PANITIA KHUSUS HAK ANGKET KOMISI PEMBERANTASAN KORUPSI (KPK) DI MEDIA ONLINE DETIK.COM - Sari, Indah; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Westerstahl divides objectivity into two dimensions, factuality and impartiality. In the theory, there is agenda setting theory that tends to reveal media alignments through the selection of issues and their characteristics that do not present the full reality but only prioritize the media interests. News about Pansus Hak Angket KPK has a number of factors that encourage an issue to have a news value including significance and magnitude. Making the news about Pansus Hak Angket KPK was widely reported, one of the most was in the online media Detik.com. For this reason, this research aims to find out the level of factuality and impartiality applied in the news about Pansus Hak Angket KPK in online media Detik.com. This type of research is quantitative with a content analysis approach. The news samples studied were 141 news periods from 30 May 2017 to 14 February 2018. The types of data collected were primary and secondary data. Primary data obtained from coding sheets by two Coder. The technique of measuring data uses the Guttman scale. With the data analysis techniques using syntax units. Based on the results of research that has been carried out from the four indicators of objectivity studied, it was obtained: First, the news completeness indicator was 80.85%. Second, the news source indicator is 98.94%. Third, the balance indicator is 12.06%. Fourth, the neutrality indicator is 49.29%. The results of the study indicate that Detik.com is a media that tends to report about Pansus Hak Angket KPK objectively. Keywords : Objectivity, Agenda Setting, Content Analysis, News